DNA nanostructure-based fluorescence thermometer with silver nanoclusters. (16th May 2018) - Bu, Congcong; Mu, Lixuan; Cao, Xingxing; Chen, Min; She, Guangwei; Shi, Wensheng
Abstract: DNA nanostructure-based fluorescence thermometers were fabricated by linking fluorescent silver nanoclusters (AgNCs) and guanine-rich（G-rich）DNA chains via a thermally sensitive DNA stem-loop at terminals 5′ and 3′. Variations of temperature alter the distance between the AgNCs and G-rich DNA chain, affecting the interaction between them. As a result, the intensity of fluorescence emission from the AgNCs at 636 nm can be sensitively modulated. It was found that the intensity of such red emission is more temperature sensitive than the equivalent green emission at 543 nm; sensitivity of −3.6%/°C was achieved. Through variation of the melting temperature of the DNA stem-loop, the response temperature range of the thermometers could be readily adjusted. Novel DNA nanostructure-based fluorescence thermometers as described in this work are anticipated to be able to measure the temperature of biological systems at small scales—even a single cell.